2021
DOI: 10.1001/jamanetworkopen.2021.18526
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hashimoto Thyroiditis in Adults With Papillary Thyroid Cancer and Its Association With Cancer Recurrence and Outcomes

Abstract: IMPORTANCE Hashimoto thyroiditis (HT) has been suggested to be associated with papillary thyroid cancer (PTC) development. However, its association with PTC progression remains unclear.OBJECTIVE To examine the association between HT and PTC presentation and outcomes. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study included a review of patients aged 18 to 75 years who had pathologically confirmed PTC treated at a single center in China

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 27 publications
5
39
2
1
Order By: Relevance
“…Furthermore, our findings showed that PTC patients with HT were also less likely to develop recurrence and have a higher 20-year survival rate, which were in agreement with prior studies [ 41 , 66 ]. Although we did not find the presence of HT indicates lower disease-specific deaths, a recent study by Hu et al reported that patients with HT had lower rates of tumor recurrence, and lower disease-related mortality compared with patients without HT [ 79 ]. Kashima et al [ 13 ] reported a 0.7% cancer specific mortality and a 95% relapse-free 10-year survival rate in patients with HT compared to a 5% mortality and 85% relapse-free 10-year survival rate without chronic thyroiditis.…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, our findings showed that PTC patients with HT were also less likely to develop recurrence and have a higher 20-year survival rate, which were in agreement with prior studies [ 41 , 66 ]. Although we did not find the presence of HT indicates lower disease-specific deaths, a recent study by Hu et al reported that patients with HT had lower rates of tumor recurrence, and lower disease-related mortality compared with patients without HT [ 79 ]. Kashima et al [ 13 ] reported a 0.7% cancer specific mortality and a 95% relapse-free 10-year survival rate in patients with HT compared to a 5% mortality and 85% relapse-free 10-year survival rate without chronic thyroiditis.…”
Section: Discussioncontrasting
confidence: 89%
“…Our study implies that the clinicopathological features of PTC/HT(+) are different from those of PTC/HT(-), which is similar to other results ( 7 9 , 19 , 20 ) In addition, our result indicates that lncRNAs and mRNAs may play an important role in establishing the different clinical characteristics between patients with PTC/HT(+) and PTC/HT(-). If we can find out the specific mechanism, it may bring new clinical methods to the diagnosis and treatment of PTC combined HT.…”
Section: Discussionsupporting
confidence: 85%
“…The association between HT and PTC was first described in 1955. Since then, an increasing number of studies have investigated the association between HT and PTC, and many studies showing that the clinicopathological features of PTC complicated with HT [PTC/HT (+)] are different from those of PTC without HT [PTC/HT (-)] ( 7 9 ). Compared with PTC/HT (-), PTC/HT (+) is associated with a lower VI lymph node metastasis rate, lower-stage disease, and less disease persistence, but the molecular mechanisms underlying these differences remain unelucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported a considerably better prognosis of DTC when HT is also present; however, these data are not uniform in the various studies, as some report a greater presence of multifocal carcinomas and a similar recurrence rate to non-HT tumors ( 20 , 21 ), while others show a greater presence of microcarcinomas, with a smaller average tumor size and a lower incidence of lymph node metastases and extrathyroidal extension, leading to significantly better disease-free survival for DTCs with concomitant HT than for those without HT ( 16 , 22 , 23 , 38 ).…”
Section: Discussionmentioning
confidence: 99%